2016
DOI: 10.1039/c5lc01499a
|View full text |Cite
|
Sign up to set email alerts
|

3D high throughput screening and profiling of embryoid bodies in thermoformed microwell plates

Abstract: 3D organoids using stem cells to study development and disease are now widespread. These models are powerful to mimic in vivo situations but are currently associated with high variability and low throughput. For biomedical research, platforms are thus necessary to increase reproducibility and allow high-throughput screens (HTS). Here, we introduce a microwell platform, integrated in standard culture plates, for functional HTS. Using micro-thermoforming, we form round-bottom microwell arrays from optically clea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 32 publications
0
50
0
Order By: Relevance
“…The resulting HTS screen identified novel compounds to direct differentiation. Taken together, these works show that HTS in simplified realistic microengineered environments is possible, and that it may provide important advantages to the drug discovery process [17].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…The resulting HTS screen identified novel compounds to direct differentiation. Taken together, these works show that HTS in simplified realistic microengineered environments is possible, and that it may provide important advantages to the drug discovery process [17].…”
Section: Introductionmentioning
confidence: 73%
“…Spheroid culture has emerged as an important tool to study cancers in realistic environments, in which cells adhere to each other forming a 3D body. Microfabrication approaches were recently developed by Vrij et al to scale spheroid culture up toward HTS levels by using a plastic thermoforming process to create dense arrays of microwells within a microplate [17]. The resulting structures allows seeded cells to cluster and form 3D bodies that can then be assayed with a large number of replicates for each drug to be screened.…”
Section: Introductionmentioning
confidence: 99%
“…This is characteristic for stem cells. It was shown that ESCs form aggregates called embryoid bodies [15]. Embryoid bodies can be obtained particularly easily in ESCs cultured in suspension.…”
Section: Discussionmentioning
confidence: 99%
“…There are several methods for cell spheroid formation other than the microfluidic approach including magnetic levitation [34], 3D-bioprinting [35], hydrophobic surfaces [36], matrix-on-top [37], matrix-embedded [38], polymeric aqueous two-phase system [39], floating liquid marbles [40], multiwell plates [41], bioreactor flasks [42], liquid overlay [43] and HD techniques [36]. Some of these techniques such as HD and multiwell plates are laborious while some others like 3D-bioprinting and magnetic levitation are costly and still lack the standard protocols.…”
Section: Conventional Methods For Spheroid Formationmentioning
confidence: 99%